Novel enzyme-fermentation process for bioconversion of restaurant food waste into isomaltooligosaccharide-and L-lactic acid-enriched animal feed - Bilal, Muhammad; Niu, Dandan; Wang, Zhengxiang (Frontiers in Sustainable Food Systems, 2024)
Introduction Considering the valuable organic fraction contained, restaurant food waste (RFW) has attracted more attention as an alternative substrate for animal feed production. In this work, a new enzyme-fermentation process (EFP) for diverting RFW into synbiotic animal feed was developed, and its economic and environmental benefits were evaluated. Methods The process initiated with enzymatic hydrolysis of RFWs, intending to convert starch into isomaltooligosaccharides (IMOs) via simultaneous saccharification and transglycosylation (SST). Subsequently, the hydrolysate underwent fermentation with engineered Pichia pastoris GSL to form L-lactic acid (L-LA) from the free glucose and to biologically enhance the nutritional value. Results and discussion The results indicated that employing the EFP yielded the highest IMOs levels, ranging from 17.10–38.00 g/L. Simultaneously, the process achieved the maximum L-LA concentration (20.75–27.16 g/L), with a conversion efficiency of 0.64–0.78 g/g. Additionally, 5.0–8.5 g/L of yeast biomass was generated. Economic estimates elucidated that the cost of RFW-derived animal feed through EFP was about 0.16/kg, signifying a substantial cost reduction (≥ 70%) compared to traditional feeds. Achieving complete conversion of RFW into animal feed while eliminating residual waste highlights the significant environmental benefits and the compatibility of the present technology with the zero-waste concept.